2014
DOI: 10.1523/jneurosci.0612-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Correlates of Visual Working Memory in the Corvid Endbrain

Abstract: The concept of working memory is key to cognitive functioning. Working memory encompasses the capacity to retain immediately past information, to process this information, and to use it to guide goal-directed behavior. Corvid songbirds are renowned for their high-level cognitive capabilities, but where and how visual information is temporarily retained by neurons in the avian brain in a behaviorally relevant way remains poorly understood. We trained four carrion crows (Corvus corone) on versions of a delayed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 32 publications
4
72
1
Order By: Relevance
“…Similar maximal accuracy levels have been reported for amphibians [6]. However, we know that crows can perform close to 100% correct [27,28,30]. Given that the tested numerical distances between match and non-match numerosities were much larger compared with previous monkey and human studies [45,46], an alternative explanation is that the crows did not exploit the full capacity of their ANS.…”
Section: (A) Analogue Number Representations In Crowssupporting
confidence: 76%
“…Similar maximal accuracy levels have been reported for amphibians [6]. However, we know that crows can perform close to 100% correct [27,28,30]. Given that the tested numerical distances between match and non-match numerosities were much larger compared with previous monkey and human studies [45,46], an alternative explanation is that the crows did not exploit the full capacity of their ANS.…”
Section: (A) Analogue Number Representations In Crowssupporting
confidence: 76%
“…NCL neurons carried an internal, stimulus-independent signal that was predictive of error and type of error. These results underscore the role of corvid NCL [4][5][6][7] in synthesizing external multisensory information and internal mnemonic data needed for executive control of behavior.…”
Section: Discussionmentioning
confidence: 62%
“…The electrodes targeted the NCL. Tracing electrode tracks of an identically implanted crow used for a different study (25,26) confirmed that recording locations were within NCL. Cryostat sections were immunohistochemically stained for tyrosine-hydroxylase to identify dopaminergic cells, which characterize the NCL (25).…”
Section: Methodsmentioning
confidence: 68%
“…The birds' lineage diverged from mammals 300 Mya (19), at a time when the neocortex had not yet developed from the pallium of the endbrain. Instead, birds developed different pallial parts as dominant endbrain structures (20,21) based on convergent evolution, with the nidopallium caudolaterale (NCL) as a highlevel association area (22)(23)(24)(25)(26). Where and how numerosity is encoded in vertebrates lacking a neocortex is unknown.…”
mentioning
confidence: 99%